NiTiO3 powders obtained by polymeric precursor method: Synthesis and characterization - Lopes, K. P.; Cavalcante, L. S.; Simões, Alexandre Zirpoli [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Leite, E. R. (Elsevier B.V. Sa, 2009)
Nickel titanate (NiTiO3) powders were synthesized by the polymeric precursor method after thermal treatment at different temperatures for 2h in air atmosphere. The decomposition of the precursors was monitored by differential scanning calorimetry and thermogravimetric analysis. The NiTiO3 powders presented a reduction in the specific surface area and increase of the average particle size with the evolution of the temperature. The structural evolution of NiTiO3 phase was accompanied by X-ray diffraction and Fourier transform Raman spectroscopy. By scanning electron microscopy was revealed the agglomerated nature of very line particles of NiTiO3, powders annealed from 600 to 1000 C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Inorganic materials; Chemical synthesis; Microstructure; Crystal structure; X-ray diffraction